Rational use of essential drugs in the public and private sector PHC facilities in Bangladesh current situation and future directions - Ahmed, Syed Masud; Islam, Shafayetul (BRAC Research and Evaluation Division (RED), 2019)
In Bangladesh, the National Drug Policy (NDP) of 1982 was instrumental in improving the supply of quality essential drugs at an affordable price, especially in the early years However, over time, evidences exist about the deterioration of situation both in terms of availability of essential drugs as well as rational Lise of drugs. This study examined the current status of the outcome objectives of the NDP in terms of availability, affordability and rational use of drugs in the primary healthcare (PHC) facilities in Bangladesh. To address this, the study covered a random sample of Upazila Health Complexes (UHC) in the rural areas (n=30) and a convenient sample of Urban Clinics (UC) in the Dhaka Metropolitan area (n=20) for observation, exit-interview and minimarket survey to collect data on WHO core drug use indicators in health facilities. Findings reveal the availability of essential drugs for common illnesses to be poor, varying from 6% in the UHCs to 15% in the UCs. Drugs dispensed out of total prescribed was higher in UHCs (76%) compared to lJCs (44%). Dispensed drugs were not labeled properly, though 73% of the patients/care-givers reported to have understood the dosage schedule. Copy of an Essential Drugs List was available in 55% UCs and 47% UHCs with around 2/3rd drugs being prescribed from it. Polypharmacy was higher in the UCs (46%) than in the UHCs (33%). An antibiotic was prescribed in 44% of the encounters, more frequently for fever (36-40%) and common cold (26-34%) than for lower respiratory tract infection including pneumonia (10-20%). Prices of key essential drugs differed widely by brands (500% or more), seriously compromising the affordability for common people. 'This, the availability, affordability and the rational use of drugs have remained an illusory target to achieve in Bangladesh even 27 years after passing the much acclaimed NDP of 1982.